Students’ Perceptions on Using Google Classroom in Learning English at Madrasah Aliyah Hasanah Pekanbaru - Nur Hidayah Siregar; Syofia Delfi; M. Syarfi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The aim of this research is to find out students’ perceptions on using Google Classroom in learning English at Madrasah Aliyah Hasanah Pekanbaru. By applying the descriptive-quantitative method, the subjects of this study were all grade students of Madrasah Aliyah Hasanah Pekanbaru with the total of 76 students. The research instrument was a questionnaire adapted from previous research by Hidayat et al (2009), Shaharanee et al (2016), Astuti, T., & Indriani, L. (2020), and Salam, U. (2020). The researcher used IBM SPSS Statistics 25 to analyze the data. Findings showed that several factors influence the students' online learning process, namely, ease of access, usefulness, communication and interaction, ease of use, and satisfaction. Most students are classified into the “high” classification of perception with a total mean score of 3.87. It indicates that most students gave positive responses toward using Google Classroom in learning English. The students agreed that Google Classroom is suitable to use continuously in learning English because it is helpful and useful application, easy to use, have many interesting features and satisfied to learning English. This research implies that Google Classroom can be considered as one of the alternative learning platforms that can be used by schools during pandemic situations and other emergency situations to learn English.